Chinese behind the wheel: Factors affecting their satisfaction with international self- drive holidays. (September 2018) - Wu, Mao-Ying; Pearce, Philip L.; Li, Qiucheng
Abstract: This study seeks to assess the factors influencing the satisfaction of Chinese tourists when they undertake self-drive international vacations. There are few existing studies about this independent travel market. Semi-structured interviews were undertaken to gather initial views about the attributes contributing to self-drive satisfaction. A questionnaire-based survey was then employed in Shanghai. Multiple linear regression analysis was used to test the factors which significantly affected tourists' satisfaction. Analysis of the data reflected some of the findings from limited previous studies of other international groups: the scenery, road facilities, and available activities all have a significant positive impact on satisfaction. However, for the Chinese drive tourists, the responses of the local community to their trip, as well as key environmental issues, notably air quality, are distinctively important concerns. Implications are identified for international destination management organizations which are interested in promoting to and developing this self-drive Chinese market. Highlights: Assesses factors influencing Chinese outbound self-drive tourists' holidays The scenery, road facilities, and on-site activities are influential Community hospitality significantly affects tourists' satisfaction The air quality of the destination forms as an important attribution Implications to seize the Chinese self-drive tourism market are offered